Effect of Transplanting Date and Spacing on Seed Production of Broccoli (Brassica oleracea var. italica Plenck) at Chitwan, Nepal - Shrestha, Saraswati; Shribastava, Arvind; Sharma, Mohadatta (Journal of Agriculture and Environment, 2023)
A study was conducted at the Agriculture and Forestry University, Rampur, Chitwan during the winter season, to find out the suitable transplanting dates and spacing for quality seed production of broccoli (Brassica oleracea var. italica) Cv. Calabrese. The experiment was laid out in split plot design with three replications, where main plot treatment consisted of transplanting dates (November 1, November 15 and November 30) and sub plot treatment consisted of spacing (60 cm × 50 cm, 60 cm × 60 cm, 60 cm × 75 cm). Since transplanting time and spacing affect vegetative traits, which are very important for seed yield. The highest seed yield (1.09 mt./ha) was obtained with November 1st planting at the spacing of 60 cm × 50 cm. So that transplanting date of November 1st with spacing 60 cm × 50 cm is better for seed production of broccoli in plain areas of Chitwan, Nepal.